Classes hospitalares: análise dos anais do congresso nacional de educação – EDUCERE (2008-2019) - Favoretto, Irlaine Aparecida (2021)
Considering that the hospital classes enable the beginning, or the continuity, of the formal/systematized learning process by providing access to children and adolescents who are away from the conventional classroom due to a hospital admission, this research aims to analyze the papers published in the database of the National Congress on Education - Educere-PUCPR, in the period from 2008-2019, which deal with this theme. The eligibility criterion was that the work, regardless of the modality (round table, oral communication and poster) and the axes of the event, presented the descriptor "hospital class(es)" in the title, abstract and/or key words. Fifty-six papers were found whose analysis was performed with the help of the Alceste® textual statistics software, and with the support of authors who investigate the interface between Education and Health, such as Barros (1999), Barros, Gueudeville and Vieira (2011), Fonseca (1999, 2003, 2020), Fonseca, Araújo and Ladeira (2018), Paula (2004, 2007a, 2007b, 2011, 2015a, 2015b), Paula et al. (2012), Passeggi, Rodrigues, and Furlanetto (2019), and Rocha and Passeggi (2010). The data collected allowed to ascertain the annual distribution and to consider the scientific modality. The results pointed to three thematic trends: 1) works focused on the figure of the teacher, by emphasizing struggles of these professionals, through movements that highlight the identity and tensions of the class; 2) works that focus on the articulations between the fields of education and health, by highlighting the challenges of the implementation of this segment of education, both nationally and statewide; 3) works that indicate a movement by authors who are beginning in the theme. In view of these results, we emphasize the importance of research that analyzes the knowledge produced and aims to provide subsidies for reflections about the production of a particular scientific area.